Characterization of surface modified glycerol/silk fibroin film for application to corneal endothelial cell regeneration. Issue 4 (4th March 2019) - Song, Jeong Eun; Sim, Bo Ra; Jeon, Yoo Shin; Kim, Han Sol; Shin, Eun Yeong; Carlomagno, Cristiano; Khang, Gilson
Abstract: Corneal endothelial cells (CEnCs) play a fundamental role in maintaining the transparency of the cornea. CEnCs lose their full proliferating capacity when tissue damages occur. The loss in proliferation rate is associated with corneal edema and decrease in visual acuity, leading in severe cases, to blindness. In these situations, a corneal transplant is usually needed to restore the original tissue functions. Tissue engineering is an efficient alternative for the production of implantable films, which can regenerate the tissue functions regulating at the same time the immune-response. In this study, we proposed a stable and transparent film, composed of silk fibroin modified with glycerol (G/SF), as a potential substrate for corneal endothelial cells regeneration. Our results confirmed that G/SF films have a uniform structure, rougher surface and lower thickness respect to the SF film. In vitro tests show that G/SF films can induce a slight increase in CEnCs initial adhesion and proliferation rate if compared with the SF film. Morphology and gene expression evaluations demonstrated that the bioactive effects of silk fibroin were not affected by the presence of glycerol. For this reason, the G/SF films are suitable as CEnCs carrier and promising for the corneal damages treatments.